LEARNER-CENTERED TEACHING: WHAT MAKES IT EFFECTIVE - Endang Darsih (University of Kuningan, 2018)
Learner-centered teaching is a teaching approach that is increasingly being encouraged in education. In Indonesia, learner-centered teaching has been an obligation for teachers to be implemented since the government decided to try out the new designed curriculum, the 2013 curriculum. However, it is not always effective since teachers are lack of creativity, lack of responsibility and knowledge. Therefore, this study was sought to find out teacher’s efforts and their roles in implementing learner-centered teaching effectively. The study involving two English teachers revealed that several efforts done by teachers in learner-centered teaching are; 1) let the students do the hard messy work of learning because they are not passive recipients of knowledge, 2) give autonomy and responsibility to students for material they learn and their own learning in general, 3) use highly engaging core content that meets the needs of the students, 4) give feedback to help students to improve, and 4) utilize multiple teaching techniques appropriate for student learning goals. Several roles of teachers in learner-centered teaching are as guides, facilitator and coaches. Teachers also play important roles in creating an environment that fosters students’ learning, accommodates different learning styles, and motivates students to accept responsibility for learning.Keywords: Learner-centered teaching, teaching approach, teachers’ efforts roles